Fine structure of K-excitons in multilayers of transition metal dichalcogenides. (28th February 2019) - Slobodeniuk, A O; Bala, Ł; Koperski, M; Molas, M R; Kossacki, P; Nogajewski, K; Bartos, M; Watanabe, K; Taniguchi, T; Faugeras, C; Potemski, M
Abstract: Reflectance and magneto-reflectance experiments together with theoretical modelling based on the k ⋅ p approach have been employed to study the evolution of direct bandgap excitons in MoS2 layers with a thickness ranging from mono- to trilayer. We observe extra excitonic resonances in MoS2 multilayers which emerge as a result of the hybridization of Bloch states of each sub-layer due to the interlayer coupling. The properties of such excitons in bi- and trilayers are classified by the symmetry of the corresponding crystals. The inter- and intralayer character of the reported excitonic resonances is fingerprinted with the magneto-optical measurements: excitonic g -factors of opposite sign and of different amplitude are revealed for these two types of resonances. The parameters describing the strength of the spin–orbit interaction are estimated for bi- and trilayer MoS2 .